PENGARUH KARAKTERISTIK ORGANISASI DAN KARAKTERISTIK INDIVIDU TERHADAP STRES KERJA DAN VOLUNTARY TURNNOVER INTENTION (STUDI PADA KARYAWATI PT. JASA RAHARJA (PERSERO) CABANG TIPE A - Nugroho, Sarlinto Adi; Sularso, Raden Andi; Prihatini, Dewi (BISMA: Jurnal Bisnis dan Manajemen, 2016)
Abstract: The purpose of this study among others, to analyze the effect of the characteristics of the organization and the individual characteristics of the stress of work and voluntary employee turnover intention PT. Jasa Raharja (Persero) Branch Type A as well as to analyze the effect of work stress on turonover intention employee of PT. Jasa Raharja (Persero) Branch Type A. This study was a research explanation. The study population was 162 employees of PT. Jasa Raharja (Persero) Branch Type A sample was 100 people. Methods of data analysis used SEM. The results showed that the organizational characteristics significantly influence employee stress PT. Jasa Raharja (Persero) Branch Type A. The individual characteristics significantly influence the stress PT. Jasa Raharja (Persero) Branch Type A. Characteristics organizations no significant effect on turnover intention Voluntary PT. Jasa Raharja (Persero) Branch Type A. The individual characteristics significantly influence the Voluntary turnover intention PT. Jasa Raharja (Persero) Branch Type A Stress significant effect on turnover intention Voluntary PT. Jasa Raharja (Persero) Branch Type A. Keywords: organizational characteristics, individual characteristics, work stress and voluntary turnover intention